Evaluation of Bactericidal Activities of LY333328, Vancomycin, Teicoplanin, Ampicillin-Sulbactam, Trovafloxacin, and RP59500 Alone or in Combination with Rifampin or Gentamicin against Different Strains of Vancomycin-Intermediate Staphylococcus aureus by Time-Kill Curve Methods - Hershberger, Ellie (American Society for Microbiology, 1999)
This in vitro study evaluated the activities of vancomycin, LY333328, and teicoplanin alone and in combination with gentamicin, rifampin, and RP59500 against Staphylococcus aureus isolates with intermediate susceptibilities to vancomycin. Ampicillin-sulbactam and trovafloxacin were also evaluated. LY333328 and ampicillin-sulbactam resulted in bactericidal activity against all isolates. The combination of gentamicin with glycopeptides showed synergistic activity, while rifampin had no added benefit.